Photo Essay: Indigenous Peoples’ Durban Climate Change (Fourth World Journal, 2011)
This photo essay examines the impact of climate change on indigenous peoples, with a focus on the United Nations Climate Negotiations held in Durban, South Africa. It highlights the human rights violations experienced by indigenous communities as a result of climate change policies and measures that often exclude their voices.